Transcriptomic Analysis of Short/Branched-Chain Acyl-Coenzyme a Dehydrogenase Knocked Out bMECs Revealed Its Regulatory Effect on Lipid Metabolism - Jiang, Ping; Iqbal, Ambreen; Wang, Mengyan; Li, Xiaohui; Fang, Xibi; Yu, Haibin; Zhao, Zhihui (Frontiers in Veterinary Science, 2021)
The acyl-CoA dehydrogenase family of enzymes includes short/branched-chain acyl-CoA dehydrogenase (ACADSB), which catalyzes the dehydrogenation of acyl-CoA derivatives in fatty acid metabolism. Our previous findings suggested that ACADSB was a critical candidate gene affecting milk fat synthesis by comparing the transcriptome in bovine mammary epithelial cells (bMECs) from Chinese Holstein dairy cows producing high-fat and low-fat milk as well as gene functional validation studies on the cellular level. In the present study, ACADSB in bMECs was knocked out (KO) using a CRISPR/Cas9 system, and mRNA transcriptome was further sequenced to verify the function of the ACADSB gene and analyze its correlation with lipid metabolism. The findings revealed that 15,693 genes were expressed, 1,548 genes were differentially expressed genes (DEGs), and 6,098 GO terms were enriched, of which 637 GO terms were greatly enhanced, such as phospholipid-translocation ATPase activity (GO:0004012), lipoprotein lipase activity (GO:0004465), acyl-CoA desaturase activity (GO:0016215), and so on. The analysis by KEGG showed that DEGs were distributed over 247 pathogens, of which 49 were significantly enriched, including the metabolism of fatty acids (PATH: 01212), metabolism of glycerolipid (PATH: 00561), and signaling of adipocytokines (PATH: 04920). The CHOL, TGs and FFA contents in bMECs were reduced when the ACADSB gene was knocked out. The RT2 Profiler PCR array also revealed that the loss of the ACADSB gene changed the expression levels of functional genes involved in lipid metabolism, including ACADL, ACOX2, ACAT2, and FABP3. In conclusion, the current findings show that ACADSB is a key regulator of lipid metabolism in bMECs. The ACADSB−/− bMECs could also be useful genetic material and tools for future research into gene functions related to lipid and fatty acid metabolism. It will be valuable for revealing the gene regulatory roles and molecular mechanisms in milk fat synthesis.